IL-33 receptor inhibition in subjects with uncontrolled asthma: A randomized, placebo-controlled trial - Crim, Courtney; Stone, Sally; Millar, Valerie; Lettis, Sally; Bel, Elisabeth H.; Menzies-Gow, Andrew; Chanez, Pascal; Wenzel, Sally; Lugogo, Njira; Bleecker, Eugene R. (The journal of allergy and clinical immunology. Global, 2022)
Most biologics for severe asthma target only type 2 immunity. Inhibition of IL-33 signaling has the potential to target type 2 and non–type 2 pathways. This multicenter phase IIA study evaluated the safety and efficacy of GSK3772847, a human mAb directed against the IL-33 receptor (IL-33R) in subjects with moderate-to-severe uncontrolled asthma. Adults with uncontrolled asthma despite inhaled corticosteroid/long-acting β2-agonist therapy received equivalent replacement medication (open-label fluticasone propionate/salmeterol [500/50 μg, twice daily]) for 2 weeks before randomization at week 0. At weeks 0, 4, 8, and 12, participants were administered blinded placebo or 10 mg/kg of intravenous GSK3772847. At week 2, salmeterol was discontinued; thereafter, fluticasone propionate was titrated by approximately 50% on weeks 4, 6, 8, and 10. Asthma control was assessed until week 16. Participants with loss of asthma control discontinued treatment. The primary end point was loss of asthma control; secondary end points were the efficacy, safety, tolerability, pharmacodynamics, and pharmacokinetics of GSK3772847. At week 16, 56 participants (81%) and 45 (66%) receiving placebo and GSK3772847, respectively, had loss of asthma control (an 18% reduction [95% credible interval = 2%-35%]). Early loss of asthma control prevented full analysis of the secondary efficacy end points after week 4. The most frequent classes of treatment-related adverse events were cardiac disorders (n = 3 [4%] in both groups) and musculoskeletal/connective tissue disorders (with GSK3772847, n = 3 [4%]; with placebo n = 0). Target engagement of IL-33R by GSK3772847 was demonstrated. Treatment with GSK3772847 may be beneficial for patients with uncontrolled asthma. Further studies are warranted.